Editorial: New biomarkers for the diagnosis and treatment of systemic lupus erythematosus - Perl, Andras; Agmon-Levin, Nancy; Crispín, José C.; Jorgensen, Trine N. (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) is an autoimmune disease of unknown etiology with significant mortality that primarily affects females of child-bearing age. While current treatments are partially effective, they carry significant side effects. Therefore, significant unmet needs exist to identify biomarkers that can be targeted for safe and effective therapeutic intervention in SLE. A research topic centered around new biomarkers for the diagnosis and treatment of SLE attracted 15 publications with a wide range of focus and experimental design. This editorial addresses the challenges of integrating multi-omics and systems biology through machine learning.